Autophagy controls Wolbachia infection upon bacterial damage and in aging Drosophila - Hargitai, Dávid; Kenéz, Lili; Al-Lami, Muna; Szenczi, Győző; Lőrincz, Péter; Juhász, Gábor (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is a conserved catabolic process in eukaryotic cells that degrades intracellular components in lysosomes, often in an organelle-specific selective manner (mitophagy, ERphagy, etc). Cells also use autophagy as a defense mechanism, eliminating intracellular pathogens via selective degradation known as xenophagy. Wolbachia pipientis is a Gram-negative intracellular bacterium, which is one of the most common parasites on Earth affecting approximately half of terrestrial arthropods. Interestingly, infection grants the host resistance against other pathogens and modulates lifespan, so this bacterium also resembles an endosymbiont. Here we demonstrate that Drosophila somatic cells degrade a subset of these bacterial cells normally, and autophagy is required for selective elimination of Wolbachia upon antibiotic damage. In line with these, Wolbachia overpopulates in autophagy-compromised animals during aging and its presence fails to affect host lifespan, unlike in case of control flies. The autophagic degradation of Wolbachia (wolbophagy) thus represents a novel antibacterial mechanism that controls the intracellular propagation of this unique bacterium, which behaves both as parasite and endosymbiont at the same time.